FAKTOR-FAKTOR YANG MEMEPENGARUHI KUALITAS AUDIT - Nabilah Noviyanti; Efrinal - (Fakultas Ekonomi dan Bisnis Universitas Islam As-Syafi'iyah, 2023)
This study aims to determine the effect of independence and time budget pressure on audit quality during the Covid-19 pandemic. The population in this study is the Public Accounting Firm in East Jakarta and Bekasi. The sample used in this study were auditors at Public Accounting Firms in East Jakarta and Bekasi, with 34 respondents using a purposive sampling method. The independent variables of this study are independence and time budget pressure. The dependent variable of this study is audit quality during the Covid-19 pandemic. The results show that independence has no significant effect on audit quality during the Covid-19 pandemic. Meanwhile, time budget pressure has a significant negative effect on audit quality during the Covid-19 pandemic.: Independence: Independence